2021
DOI: 10.1039/d0cp03079a
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol–ethylene conversion mechanism on hydrogen boride sheets probed by in situ infrared absorption spectroscopy

Abstract: Two-dimensional hydrogen boride (HB) sheets were recently demonstrated to act as a solid acid catalyst in their hydrogen-deficient state. However, the mechanism of the catalytic process and the active sites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…48,51,54 HB nanosheets were realized experimentally in three ways: (i) decomposition of borane in H 2 ; 55 (ii) chemical vapor deposition from solid powders (B, B 2 O 3 , or NaBH 4 ) in H 2 ; 44,52,53 (iii) a cation exchange reaction with organic solvents/cation exchange resins that can provide protons. [56][57][58][59] For example, Xu et al prepared HB nanosheets on a silicon wafer via chemical vapor deposition using borane gas (5% B 2 H 6 + 95% Ar) and the nanosheets show excellent photoexcitation behavior because of the slightly opened band gap, as illustrated in Fig. 3(a).…”
Section: Hydrogenated Boron Nanosheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…48,51,54 HB nanosheets were realized experimentally in three ways: (i) decomposition of borane in H 2 ; 55 (ii) chemical vapor deposition from solid powders (B, B 2 O 3 , or NaBH 4 ) in H 2 ; 44,52,53 (iii) a cation exchange reaction with organic solvents/cation exchange resins that can provide protons. [56][57][58][59] For example, Xu et al prepared HB nanosheets on a silicon wafer via chemical vapor deposition using borane gas (5% B 2 H 6 + 95% Ar) and the nanosheets show excellent photoexcitation behavior because of the slightly opened band gap, as illustrated in Fig. 3(a).…”
Section: Hydrogenated Boron Nanosheetsmentioning
confidence: 99%
“…3(e)]. 57,59,63 According to Kondo's work, the redox potential of HB sheets is between À0.277 and À0.257 V versus the standard hydrogen electrode (SHE). 63 The reduction properties of HB nanosheets are related to H functionalization.…”
Section: Hydrogenated Boron Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the material is HB, where the hydrogen/boron atomic ratio is 1/1. Previous experiments have shown that hydrogen boride sheets have a high H 2 content (8.5 wt %) [2], unique electronic properties [3,4], solid acid catalytic properties [5,6], photoinduced hydrogen release capability [7], and a unique ability to reduce metal ions to form nanocomposites [8][9][10]. In addition, theoretical models and computer simulations demonstrate that borophane is a promising candidate for applications such as anode material, alcohol gas sensors, current limiters, and photodetectors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies on the synthesis of hydrogen boride have been carried out only for a powder sample obtained from finely dispersed MgB 2 [2][3][4][5][6][7][8][9][10]. However, hydrogen boride thin films deposited on substrates would offer better opportunities for the in-depth analysis of the physical properties and investigation of possible applications of this material.…”
Section: Introductionmentioning
confidence: 99%